Apice: Plan parcial de conexión y rehabilitación eco productivo sabana centro (2019)
This document is based on a research process on the central savanna region. This region, made up of eleven municipalities, has a large area of rural area, currently in slow development and deterioration due to the proximity of Bogotá as some have become municipalities visited only on weekends or inhabit there for greater tranquility and they have made in turn the size of the urban center increase, thus generating shops and economic activities dedicated to the daily use of this population, therefore people migrate from their municipalities to the city to find better opportunities both labor and educational.